Behaviour of single-phase self-excited induction generator during short-circuit at terminals. Issue 5 (9th October 2018) - Makowski, Krzysztof; Leicht, Aleksander
Abstract : Purpose: The purpose of this paper is to present analysis of short-circuit transients in a single-phase self-excited induction generator (SP-SEIG) for different capacitor topologies. Design/methodology/approach: The paper presents field analysis of the short-circuit problem in the SP-SEIG on the base of two-dimensional field-circuit model of the generator. Findings: The carried-out field computations of the tested SP-SEIG show that the self-excited induction generator is intrinsically protected from the results of sudden short-circuit, as output voltage and current drop rapidly to zero. Short-circuit is a problem when a series capacitor is used to improve output voltage regulation. Experimental results show that re-excitation of the generator is possible after the short-circuit is removed. Originality/value: The originality of the paper is the presented analysis of short-circuit transients at terminals of SP-SEIG. A finite elements method-based field circuit model was used. The simulation results were validated by the measurements conducted on a laboratory test setup.